2003
DOI: 10.1007/s00438-003-0856-9
|View full text |Cite
|
Sign up to set email alerts
|

A gene for a Class II DNA photolyase from Oryza sativa: cloning of the cDNA by dilution-amplification

Abstract: Ultraviolet radiation induces the formation of two classes of photoproducts in DNA-the cyclobutane pyrimidine dimer (CPD) and the pyrimidine [6-4] pyrimidone photoproduct (6-4 product). Many organisms produce enzymes, termed photolyases, which specifically bind to these lesions and split them via a UV-A/blue light-dependent mechanism, thereby reversing the damage. These photolyases are specific for either CPDs or 6-4 products. Two classes of photolyases (class I and class II) repair CPDs. A gene that encodes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 40 publications
1
36
0
Order By: Relevance
“…Bacterial strains, plasmids and media The E. coli strains NKJ3002 (phr -uvrA -recA -) (Nakajima et al, 1998), KY20 (phr -) (Hirouchi et al, 2003) and DH5α (phr + recA -) (Grant et al, 1990) were used as hosts for the cloning of rice photolyase genes, overexpression and purification of GST-photolyase fusion proteins, and complementation of the rice photolyase gene in vivo. The plasmid pGEX-4T used for the glutathione-S-transferase (GST)-fused constructs was purchased from Amersham Biosciences.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial strains, plasmids and media The E. coli strains NKJ3002 (phr -uvrA -recA -) (Nakajima et al, 1998), KY20 (phr -) (Hirouchi et al, 2003) and DH5α (phr + recA -) (Grant et al, 1990) were used as hosts for the cloning of rice photolyase genes, overexpression and purification of GST-photolyase fusion proteins, and complementation of the rice photolyase gene in vivo. The plasmid pGEX-4T used for the glutathione-S-transferase (GST)-fused constructs was purchased from Amersham Biosciences.…”
Section: Methodsmentioning
confidence: 99%
“…We have recently characterized a class II CPD photolyase from Oryza sativa (Hidema et al ,2000;Hirouchi et al, 2003;Teranishi et al, 2004). It has been indicated that Asian rice cultivars differ in their response to UV radiation in terms of growth and physiological processes (Teramura et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…these two classes of cPD photolyases share only 10% to 15% sequence similarity (75). homologs of cPD photolyases and/or 6-4 photolyases have been cloned from various plant species (1,23,54,58,65,76). characterization of laboratoryinduced UV-sensitive mutants has been a powerful tool for studying photorepair in plants.…”
Section: Photorepairmentioning
confidence: 99%
“…it was demonstrated that the photolyase-CPD complex in "Norin 1" was highly thermolabile compared with the photolyase in "Sasanishiki" (20). A cDNA clone of CPD photolyase in "Sasanishiki" was isolated (23). As shown in Fig.…”
Section: Physiological Approaches To Understanding Cultivar Differencmentioning
confidence: 99%
“…Genes encoding CPD photolyases and 6-4 PP photolyases have been identified and characterized in a range of prokaryotic and eukaryotic systems (Sancar, 2003). In plants genes encoding CPD photolyases have been identified in Arabidopsis thaliana (Ahmed et al, 1997), cucumber (Takahashi et al, 2002), rice (Hirouchi et al, 2003), spinach (Yoshihara et al, 2005), and soybean (Yamamoto et al, 2008). Genes encoding 6-4 PP photolyases have been identified in Arabidopsis and rice (Chen et al, 1994;Singh et al, 2010).…”
Section: Photoreactivationmentioning
confidence: 99%